Building a workplace writing center : a sustainable solution and practical guide - Metzenroth, Jessica Weber, 1990- (New York, NY : Routledge, 2022)
"This practical resource provides guidance for writing professionals to sustainably tackle the organizational writing challenges of any professional environment. Rooted in applied experience, Building a Workplace Writing Center guides readers through the process of developing a writing center, from assessing the needs of an organization and pitching the idea of a writing center, to developing a service model and measuring progress. Chapters explore what a writing center can offer, such as one-on-one writing consultations, tailored group workshops, and standardized writing guidance and resources. Although establishing a writing center requires time and a shift in culture up front, it is a rewarding process that produces measurably improved writing, less frustration with the writing and revision processes, and more confident, independent writers. This guide is an invaluable resource for professionals across industries and academia considering how to establish an embedded, sustainable, and cost-effective workplace writing center. It will be of particular interest to business and human resource managers considering how best to improve writing skills within their organizations"--
Keywords: Business writing; Rhetoric -- Study and teaching; BUSINESS & ECONOMICS / Business Writing; BUSINESS & ECONOMICS / Human Resources & Personnel Management